2016
DOI: 10.1038/srep27133
|View full text |Cite
|
Sign up to set email alerts
|

A novel suicide shuttle plasmid for Streptococcus suis serotype 2 and Streptococcus equi ssp. zooepidemicus gene mutation

Abstract: The mariner-based Himar1 system has been utilized for creating mutant libraries of many Gram-positive bacteria. Streptococcus suis serotype 2 (SS2) and Streptococcus equi ssp. zooepidemicus (SEZ) are primary pathogens of swine that threaten the swine industry in China. To provide a forward-genetics technology for finding virulent phenotype-related genes in these two pathogens, we constructed a novel temperature-sensitive suicide shuttle plasmid, pMar4s, which contains the Himar1 system transposon, TnYLB-1, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…An insertion mutation of SS2 ZY05719, obtained by a TnYLB-1 insertion from pMar4s, demonstrated that the capacity of anti-phagocytosis (This term means phagocytosis resistance, which comes from ref Bergman et al, 2009 ; Yamaguchi et al, 2009 ; Hsieh et al, 2016 ) compared with the wild-type strain was significantly reduced in our earlier research (Liu et al, 2016 ). The TnYLB-1 insertion site was between the T 1384 and A 1385 bases in the open reading frame (ORF) of the host specificity determinant specificity subunit ( hsdS ) gene (locus_tag ZY05719_RS06855) (Figure 1A ).…”
Section: Introductionmentioning
confidence: 60%
“…An insertion mutation of SS2 ZY05719, obtained by a TnYLB-1 insertion from pMar4s, demonstrated that the capacity of anti-phagocytosis (This term means phagocytosis resistance, which comes from ref Bergman et al, 2009 ; Yamaguchi et al, 2009 ; Hsieh et al, 2016 ) compared with the wild-type strain was significantly reduced in our earlier research (Liu et al, 2016 ). The TnYLB-1 insertion site was between the T 1384 and A 1385 bases in the open reading frame (ORF) of the host specificity determinant specificity subunit ( hsdS ) gene (locus_tag ZY05719_RS06855) (Figure 1A ).…”
Section: Introductionmentioning
confidence: 60%
“…suis mutants have been successfully identified, and Tn323 mutant has the poorest invasion ability. TnYLB‐1 insertion site of the Tn323 mutant was sequenced as previously described (Liu et al, ), and the interrupted gene was stk . The stk gene was maybe related to S .…”
Section: Resultsmentioning
confidence: 99%
“…However, mechanism of SS2 resistance to non-opsonophagocytosis are unknown and remain to be elucidated. Therefore, we screened for more pathogenesis-associated genes via a SS2 mutant library constructed previously in this lab [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phagocytosis is a crucial step of host immunity, and hence, the phagocytosis resistance ability of SS2 has attracted our attention. A transposon mutant library of ZY05719 was previously constructed in our laboratory [ 3 ]. This mutant library contained 2400 strains of SS2 mutants in total.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation